MATURE RETROVESICAL TERATOMA IN AN ADULT MALE: A CASE REPORT AND LITERATURE REVIEW - Vera, Vera; Safriadi, Ferry (Indonesian Journal of Urology, 2016)
Objective:We reported a case of mature (benign) cystic retrovesical teratoma. Retrovesical teratoma is a very rare extragonadal tumour, especially in adults, moreover in male patients. Grading and classification of teratoma is important for management and prognosis.Material & method:The patient in this study was a 49-year-old male who had chief complaints of abdominal mass and difficulty in urination. We performed Ultrasonography (USG) and Abdominal Multislice Computed Tomography (MSCT) scan on the patient. Results: USG showed a large mass in the pelvic region demonstrating a well-defined hypoechoic mass with septations at posterior of vesica urinaria. MSCT scan showed a large inhomogeneous hypodense mass with thin septations as well as multiple areas of fatty collections and coarse calcifications in pelvic region. We performed complete surgical resection per laparotomy. Grossly, the mass measured 12 x 10 x 5 cm and had rubbery consistency. Cut section of the mass revealed multilocular cystic spaces, whitish-gray walls, scattered yellowish adipose tissue collection, mucus secretions, and areas of calcifications. Pathological diagnosis of the resected tumour was a matured teratoma. The diagnosis was made because the tumour showed signs of a mature teratoma such as lined by stratified squamous and respiratory columnar eptithelium, fat and muscle tissue, nerve tissue, and calcifications. Conclusion: There were no neuroepithelium appearance. To our knowledge, this is the first retrovesical teratoma case being reported in Indonesia.